Climate of workplace fun in a retail setting - Sandell, Kyle James, author; Byrne, Zinta, advisor; Albert, Lumina, committee member; Harman, Jennifer, committee member; Kraiger, Kurt, committee member (Colorado State University. Libraries, 2015)
Workplace fun is a relatively new topic of interest for organizations and researchers alike, and one that holds much promise given the reported positive attitudinal and behavioral outcomes associated with individuals experiencing fun at work. However, no research to date has investigated shared perceptions of workplace fun, or a climate of workplace fun, within a team. A climate of workplace fun is particularly relevant in retail store settings where customer engagement and overall store performance are top priorities. Thus, the major goal of the present study is to contribute to the literature by proposing a new theoretical model of how a climate of workplace fun is fostered and what group-level outcomes result from this climate of fun. Using self-report data from retail store employees and their managers, I proposed a theoretical model of climate for fun and examined the relationships between collective coworker trust and attitudes toward workplace fun in creating an overall climate of workplace fun. In addition, I examined the relationships between this climate of fun and the group-level outcomes of engagement, store organizational citizenship behaviors, and store performance. Results indicate that both employee and manager attitudes toward fun, as well as collective coworker trust, significantly relate to climate of fun at work. Additionally, climate of fun was significantly and positively related to the store employees’ average group levels of engagement and individually-directed organizational citizenship behaviors. Climate of fun was not, however, significantly related to store performance. Results from this study highlight the potential value in creating a climate of fun in retail settings and as such, makes a significant contribution to the scientific literature on fun at work.
Keywords: group performance; workplace fun; team climate; engagement